Migration, Domestic Care Work and Public Policies on Long-Term Care in Spain - Martínez Buján, Raquel (REMHU, Revista Interdisciplinar da Mobilidade Humana, 2022)
This article explores the impact of the Covid-19 pandemic on the labour conditions of migrant workers who provide care to elderly and dependent persons in Spain. Using data from the Active Population Survey, we analyse the effects of the health crisis on the precariousness of this labour sector (measured through unemployment, underemployment and temporary employment). The figures shed light on the degradation of working conditions during the health crisis, the situation of social vulnerability experienced by female workers and the absence of effective policy responses to reverse this inequality during the pandemic. This situation of subordination is structured around the connection between the demand for care workers in private homes and the philosophy behind the public welfare system. Special emphasis is given to the effect of cash transfer programs in the process of the commodification of care.